Towards the Efficient Communication of Political Messages in Thailand: An Empirical Investigation - Laohakosol, Wilaiporn (Information Management and Business Review, 2012)
Models of consumer behavior generally posit an eclectic paradigm in which diverse elements may have an influence on an individual consumption decision. These elements might include personal experience, bias, the influence of family members and peer groups. This understanding of human behavior has been relocated from the commercial realm to the political realm with a view to helping to understand how the formation of people is voting intentions might take place and how it might be influenced. Since politics consists of a series of competing ideologies contending for the scarce resource of votes with a view to aligning state policies and the distribution of state resources along the lines of the manifesto on which a party is fighting, it follows that politicians will wish to use communication strategies to encourage as many eligible individuals as possible to vote for their policies. To date, in Thailand, most forms of political communication have been based on establishing personal contact and, hence, a form of personal relationship based on personality rather than policies. This situation is beginning to change, there is a need for those involved in determining the nature, and extent of political communications to understand which channels are appropriate for which groups of voters and which voters will not be influenced by any medium or message. Using a quantitative sample of 400 voters in four provinces of Thailand, this paper provides evidence to show that the degree to which people pay attention to political communications and to different channels varies in reasonably predictable fashions. This will enable political institutions and parties to work together to determine good and effective means of communicating their policies to the public in ways which will strengthen democratization in the country.